Best to laugh : a novel - Landvik, Lorna, 1954- (University of Minnesota Press, 2014)
"No one steps up to life's banquet, holds out her tray, and orders, "Grief, please!" Yet as a child, Candy Pekkala was served a heaping helping of it. But every buffet line has a dessert section, and when a cousin calls with a Hollywood apartment to sublet, it seems though Candy is finally offered something sweet. It's good-bye to Minnesota and hello to California, where a girl who has always lived by her wits has a real chance of making a living with them. And with that, Lorna Landvik launches her latest irresistible character onto the world stage--or at least onto the dimly lit small stage where stand-up comedy gets its start"--Inside Cover.